2018
DOI: 10.3389/fonc.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Maintaining an Extensive Library of Patient-Derived Xenograft Models

Abstract: Patient-derived xenograft (PDX) models have recently emerged as a highly desirable platform in oncology and are expected to substantially broaden the way in vivo studies are designed and executed and to reshape drug discovery programs. However, acquisition of patient-derived samples, and propagation, annotation and distribution of PDXs are complex processes that require a high degree of coordination among clinic, surgery and laboratory personnel, and are fraught with challenges that are administrative, procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 63 publications
5
66
0
Order By: Relevance
“…The patient was previously described 14 . The tumor samples were minced, mixed with matrigel, and implanted subcutaneously in the right flank of a female NOD/SCID gamma (NSG, Jackson Laboratory, Bar Harbor, ME) mouse (6-week old) to generate the patient-derived xenograft (PDX) 49 . PDX tumors were serially transplanted three times prior to being used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The patient was previously described 14 . The tumor samples were minced, mixed with matrigel, and implanted subcutaneously in the right flank of a female NOD/SCID gamma (NSG, Jackson Laboratory, Bar Harbor, ME) mouse (6-week old) to generate the patient-derived xenograft (PDX) 49 . PDX tumors were serially transplanted three times prior to being used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Another feature, source, also played a negative role in matching the genotype, different from that in tumor engraftments. Although uids source, including MPE and lymph, are proved to have a higher engraftment rate than the solid tumor tissues [32], we found that uid-derived tumor xenografts were more challenging to maintain driver genotypes from parental tumors.…”
Section: Discussionmentioning
confidence: 74%
“…Heparin was added to fluids at time of collection and cells were collected by centrifugation (1000 RPM, 5 min), washed once with ice-cold PBS and then either resuspended in growth media (DMEM:F12 + 10% FBS + 1% antibiotic/antimycotic solution) or prepared as described next for solid tumors for implantation into mice. Fresh tumor samples were cleaned and then minced, mixed with Matrigel and implanted into a subcutaneous flank of female NOD/SCID gamma (NSG, Jackson Laboratory, Bar Harbor, ME) mice to generate xenografts (26). For cell line xenografts, 10 million cells were mixed with Matrigel (1:1) and injected subcutaneously into a single flank of female NSG mice.…”
Section: Methodsmentioning
confidence: 99%